Paciente de 5 años de edad de sexo femenino fue diagnosticada con catarata congénita del Ojo Derecho, fue operada a la semana del diagnóstico, pero tiene disminuida la visión de ese ojo. - González Benítez, Deniss Jesbell (2020)
Congenital cataract is a rare condition, it is of great importance, because it can cause amblyopia due to stimulus deprivation, which is the decrease in vision caused by abnormal development or obstruction in the eye in the first stage of life; this is appreciated when the image that reaches the brain of one or both eyes is blurred; The brain then does not learn to see clearly. It is as if "disconnecting" the information from that eye, being the main cause of poor vision in children depending on the size, location and density of the cataract, the treatment is more complex than in adults since they are considered aspects of great importance such as It is the time of surgery among others. Diagnosing the congenital cataract in time would avoid serious consequences, so an ophthalmological control should be followed every six months, from the moment the presence of this opacity was detected in the lens. The objective of this clinical case is to determine the cause of poor vision in the right eye after surgery for congenital cataract presented by the patient, performing comprehensive ophthalmological and optometric diagnostic tests, such as assessment of visual acuity, reflex of bruckner, ophthalmoscopy, biomicroscopy and test lights worth. Among the results found in the study through diagnostic tests of this clinical case was amblyopia due to stimulus deprivation in the patient's right eye, so a periodic evaluation by the ophthalmologist and the optometrist is essential, in the integral visual management, mainly during the first decade of life.